THE INTERACTION ANALYSIS OF LEADERSHIP, MOTIVATION AND JOB ENGAGEMENT - Prudņikova, Ilga; Prudņikovs, Varis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of the research is to investigate the relationship between the leadership and job engagement. The study is built on research activities and there are used both theoretical and empirical methods. Qualitative and quantitative methods in the form of questionnaires are used during the study. Transformational leadership is the independent variable in this study and the instrument used to measure leadership is the Multifactor Leadership Questionnaire (Bass & Avolio, 1997). Questionnaire A Great Place To Work – What Makes Some Employers So Good And Most So Bad? (Bakingems & Kofmans, 2005) as an instrument has been used to explain what makes a company a good place to work and offers specific strategies for fostering a positive work environment and the instrument used to. The statistical programme used for the analyses and presentation of data in this research is the Statistical Package for the Social Sciences (SPSS) version 23. In conclusion: transformational leadership is more likely to increase the levels of job engagement as opposed to transactional leadership, the results from this study support interesting directions for future research.